Prestressing for Reduction of Local Vibrations in a Rotorcraft - SUWAŁA, Grzegorz; KNAP, Lech; HOLNICKI-SZULC, Jan (Engineering Transactions, 2016)
The main objective of this paper is to investigate the possibility of local structural vibration suppression via introducing initial prestressing. In order to evaluate the effectiveness of the proposed method, a two-step approach has been used. Firstly, a prestressed modal analysis was conducted to measure the influence of the prestressing on changes of eigenfrequencies and eigenmodes. In the second step, a steady dynamic analysis was performed to harmonic excitation to demonstrate the reduction of local amplitudes. Numerical experiments have been conducted on the model of a small rotorcraft. Our results indicate that introduction of initial prestressing may be used to affect natural structure frequencies and to lower the amplitude of vibrations of the structure exposed to external extortions.